Desain Penampang Sungai Way Besai Melalui Peningkatan Kapasitas Sungai Menggunakan Softwere HEC-RAS - Utami, Tri; Purwadi, Ofik Taufik; Susilo, Gatot Eko (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Way Besai river is located in Sumberjaya subdistrict, West Lampung district, Lampung. It is one of the sub river from Tulang Bawang river. Way Besai river has been used as a the electric power source, known as Besai hydropower. Besai Hydropower has decreased energy supply of 40 MW from the supply optimum can reachs 90 MW. his is due to the catcment area conditions of the Way Besai rivers are "metastable" so which effected in the shallowing of the cross-section quickly. So it needs the capacity increased of the cross-section of the river until the early condition where is the supply can reachs 90 MW.For the first step in improving the capacity of the Way Besai river needed hydraulics river simulation process that facilitated by using Hydrologic Engineering Center-River Analysis System (HEC-RAS) Program. HEC-RAS program can help to modeling the flow of cross-section of the river on the existing condition and normalization using the steady flow options and data input including maximum discharge data. The output of modeling using HEC-RAS program can be seen in the form of pictures and a table that presents the characteristics of a cross-section of the river.From the result of the analysis founded that to reach the normalization condition, needs the dredging until the elevation +713,00 level, with 2.435.590,09 m3 of volume capacity of dredging. When the water level of the river reachs Full Supply Level (FSL) elevation that is on elevation +722,00 level founded that the maximum discharge in the downstream in the amount of 57,19 m3/s, with water volume capacity in the 1.471.185,77 m3. For the Reservoir Surface Area in Way Besai river has increased with 28,6% from the exsisting condition that recorded from Sta 0+000 level until sta 3+391,45 level Keywords: Debit ,HEC-RAS, Manning calibration , Normalization, River.